1995
DOI: 10.1042/bj3050093
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cholesterol-crystallization-promoting proteins with vesicles

Abstract: In this study, the interaction of mucin and concanavalin A-binding proteins isolated from human bile with cholesterol/phospholipid vesicles was investigated. Using resonance energy transfer assays originally developed by Struck, Hoekstra and Pagano [(1981) Biochemistry 20, 4093-4099], no significant protein-induced fusion or aggregation of vesicles was demonstrated. Instead of fusion, these proteins induced destabilization of cholesterol/phospholipid vesicles, as monitored by release of entrapped carboxyfluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a recent study using similar fluorescent assays without validation by microscopy or light scattering, de Bruijn et a1 showed no effect of mucin on vesicle aggregation or fusion. 40 The authors did show that both mucin and concanavalin Abinding glycoproteins were able to induce vesicle disruption. However, these investigators failed to examine vesicle fusion and aggregation in the initial 24 hours, whereas we have shown that the major acceleration of these events by mucin occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using similar fluorescent assays without validation by microscopy or light scattering, de Bruijn et a1 showed no effect of mucin on vesicle aggregation or fusion. 40 The authors did show that both mucin and concanavalin Abinding glycoproteins were able to induce vesicle disruption. However, these investigators failed to examine vesicle fusion and aggregation in the initial 24 hours, whereas we have shown that the major acceleration of these events by mucin occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of gallstone disease consists of complex steps involving the presence of cholesterol supersaturation of the gallbladder bile, lipid-vesicle formation and aggregation, which culminates in the phase separation of cholesterol and the nucleation of cholesterol crystals [1][2][3][4][5][6]. Although a variety of factors affect this process, few investigations have compared the potencies of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Under our conditions, the physico-chemical state of the MB solution may have been more physiological, suggesting that the failure of CABG to affect lipid distribution represents the physiological state. de Brujin et al [6] reported that the nucleation-promoting action of CABG is mediated, in part, by the vesicle disruption, using a unique vesicle-monitoring system with carboxyfluorescein. Thus the cholesterol-crystallization-promoting action of CABG, which occurs under physiological circumstances, could not be based on the redistribution of lipids among biliary lipid particulate species, but seemingly on the alteration of cholesterol metastability within individual vesicular lipid bilayers Such an alteration in the physico-chemical state of the vesicular lipids could lead to the enhancement of cholesterol-crystal formation.…”
Section: Figure 7 Dose Dependence Of the Promoting Activity Of Cholesmentioning
confidence: 99%
See 1 more Smart Citation